Haiti and the politics of governance and community responses to Hurricane Matthew - Marcelin, Louis Herns (Disaster Health, 2016)
This article examines disaster preparedness and community responses to Hurricane Matthew in semi-urban and rural towns and villages in Grande-Anse, Haiti. Based on an ethnographic study conducted in the department of Grande-Anse one week after the hurricane made landfall in Haiti, the article focuses on the perspectives of citizens, community-based associations and local authorities in the affected areas. Sixty-three (63) interviews and 8 community meetings (focus groups) were conducted in 11 impacted sites in 8 communes. Results suggest that preexisting conditions in impacted communities, rather than deliberate and coordinated disaster management strategies, shaped levels of preparedness for and response to the disaster. Affected populations relied primarily on family networks and local forms of solidarity to attend to basic needs such as shelter, health and food. The main argument presented is that Haiti, by virtue of its geographic location, lack of resources, institutional fragility and vulnerability, must systematically integrate community-based assets and capacities in its responses to and management of disasters. Further, it is critical for the government, Haitian institutions, and society to apply integrated risk reduction and management and disaster preparedness measures in all aspects of life, if the country is to survive the many disasters to come in a time of climate change. These measures should be embedded in recovery and reconstruction efforts after Hurricane Matthew.